96 Well Microtitre Plate DNA Microarray for Fast Throughput of Bacteria Identification in Mastitic Milk Samples. (2015) - Green, J.; Bednar, S.; Klapproth, H.; Brandstetter, T.; Rühe, J.
Abstract: Mastitis in cattle is an inflammation of the udder that can be caused by a number of bacterial pathogens. Standard testing requires a series of tests to accurately identify the cause. Mastitic milk cannot be sold and the treatment usually involves a course of antibiotics during which time the milk can also not be sold so a fast identification of the pathogen involved is essential to reduce lost revenue. A DNA microarray was designed to identify the pathogens that could be responsible for mastitis. A 6 x 6 grid of oligonucleotides was covalently immobilised (by use of a surface attached polymer network) onto the untreated surface of each well of a 96 well microtitre plate[1] . DNA extracted from mastitic milk samples was amplified using Cy5 labelled primers and subsequently hybridised to the immobilised probes on the microarray. A standard ELISA plate washer was used to wash the microtitre plate and the signals from the bound PCR products were read in a commercially available reader (FLAIR). Using the species probes that give the strongest and weakest signals, S.Aure_35p ( Staphylococcus aureus ) and E.coli_448p ( Escherichia coli ) respectively the hybridisation signal variation from well to well was investigated The microarray can be regenerated (removal of the bound amplification products) by a hot wash cycle and then reused. To test the stability of the probes over subsequent cycles of hybridisations and regenerations a Cy3 labelled oligonucleotide was added to all the spots printed on the array and the array was subjected to 10 rounds of mock hybridisation and regeneration cycles. After 10 cycles there was only a minor loss of signal.